مسیحی -مسلم مناظرے :ٹموتھی اور خلیفہ المھدی کے ما بین بحث کا مطالعہ (Al-Qamar, 2018)
The discussion or debate for polemic reasons, equipped with certain arguments, held to counter religious rivals is called disputation. In the early Islamic era, this tradition was not as prominent as it was in the Umayyad or Abbasid times; hence it flourished among the non-Muslims due to expansion of Islamic rule, and conversion of great numbers of non-Muslims to Islam. During this period, many polemics writings against Islam floated at the surface of literary milieu. Among them is “Timothy I”, which intended to provide a polemic strategy to counter Islam intellectually. The key “arguments” of this “Disputation” revolve around the acceptance, or otherwise, of the prophethood of the Prophet Muhammad (ﷺ), His attributions in the Bible, the prophecies of the Bible about the coming of Prophet Muhammad, and the similarity of the prophetic traits between Prophet Muhammad and other prophets. The scope of this article is to take a glance of arguments and major polemic points of the mentioned “disputation”.
Keywords: Christian-Muslim Polemics; Timothy; al-Mahdī